Bioleaching of low-grade nickel sulphide ore at elevated pH - Cameron, Rory (Université d'Ottawa / University of Ottawa, 2011)
This thesis examines the bioleaching of six different Canadian nickel sulphide ores at pH levels above what is generally considered optimum (~ 2). The majority of work discussed in this thesis was conducted with a low-grade metamorphosed ultramafic nickel sulphide ore from Manitoba, Canada (Ore 3), which is not currently exploitable with conventional technologies. The ore contains 21% magnesium and 0.3% nickel. Nickel is the only significant metal value, and is present primarily as pentlandite. A substantial fraction of the magnesium is present as the serpentine mineral lizardite, making processing difficult with conventional pyro- and biohydrometallurgical techniques. The work with this ore has two equally important objectives: to minimize magnesium mobilization and to obtain an acceptable level of nickel extraction. Batch stirred-tank bioleaching experiments were conducted with finely ground ore ( 147 µm) with temperature and pH control. The first phase of experimentation examined the effect of pH (2 to 6) at 30 °C, and the second phase examined all combinations of three pH levels (3, 4 and 5) and five temperatures (5, 15, 22.5, 30, and 45 °C).
Keywords: bioleaching; pentlandite; bio-oxidation; nickel sulphide ore; nickel sulfide ore; stirred-tank reactor; serpentine; ultramafic